Instagram Social Media Management Strategy As A Creative Media To Increase School Reach And Image - Aini Mahfudhoh; Sulistyorini Sulistyorini (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze Instagram social media management strategies as a creative medium to enhance the reach and image of SMA IT Al-Hikmah Bence Blitar. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation. The findings reveal that successful school branding through Instagram is supported by three main aspects: content planning that is integrated with school programs, collaborative implementation involving teachers, students, and the foundation’s media team, and routine evaluation based on Instagram Insight data. Instagram functions not only as a promotional tool but also as a collaborative space that strengthens student engagement, builds parental trust, and affirms the school’s Islamic identity. The study concludes that structured, collaborative, and consistent social media management can serve as a strategic instrument to strengthen the image and competitiveness of educational institutions.